Penerapan Web Service pada Integrasi Database Simperpus dan SIAK Menggunakan Rest API - Nugroho, Setiya; Primadewi, Ardhin (Universitas Muhammadiyah Magelang, 2020)
Library Information Systems and Academic Information Systems that are not integrated with each other have resulted in duplication and inconsistency of data. This study aims to integrate databases by implementing web services in both systems. Simperpus uses the Rest Client and SIAK uses the Rest Server. The exchange of data between the server utilizes JSON. This research uses UML as a system design modeling with several diagrams, namely use case diagrams, class diagrams, sequence diagrams, activity diagrams, component diagrams, and deployment diagrams. Writing programming language in the study is the Codeigniter framework with MySQL database. The test results showed that the process of sending data in JSON format from SIAK to Simperpus obtained a response time of 137 ms.